2012
DOI: 10.1038/srep00913
|View full text |Cite
|
Sign up to set email alerts
|

Gassing in Li4Ti5O12-based batteries and its remedy

Abstract: Destructive gas generation with associated swelling has been a major challenge to the large-scale application of lithium ion batteries (LIBs) made from Li4Ti5O12 (LTO) anodes. Here we report root causes of the gassing behavior, and suggest remedy to suppress it. The generated gases mainly contain H2, CO2 and CO, which originate from interfacial reactions between LTO and surrounding alkyl carbonate solvents. The reactions occur at the very thin outermost surface of LTO (111) plane, which result in transformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
314
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 316 publications
(325 citation statements)
references
References 52 publications
11
314
0
Order By: Relevance
“…The hydroxyl groups are Lewis‐acid sites which are considered to be able to initiate the decomposition of electrolyte solvent. Due to this high catalytic activity, anatase‐TiO 2 is considered as an undesired phase and potentially triggers severe side reactions and gassing 34, 35. Interestingly, for the hydrothermal treated LTO with 0.008 mol L −1 Na 2 S aqueous solution, the A/L value is always zero from 4 to 12 h, indicating that Na 2 S prevents the formation of anatase‐TiO 2 phase on the LTO surface.…”
Section: Resultsmentioning
confidence: 99%
“…The hydroxyl groups are Lewis‐acid sites which are considered to be able to initiate the decomposition of electrolyte solvent. Due to this high catalytic activity, anatase‐TiO 2 is considered as an undesired phase and potentially triggers severe side reactions and gassing 34, 35. Interestingly, for the hydrothermal treated LTO with 0.008 mol L −1 Na 2 S aqueous solution, the A/L value is always zero from 4 to 12 h, indicating that Na 2 S prevents the formation of anatase‐TiO 2 phase on the LTO surface.…”
Section: Resultsmentioning
confidence: 99%
“…Many previous works have reported that the voltage corresponding to the reaction of LTO with lithium (1.55 V vs. Li/Li + ) is too high to reductively decompose electrolytes. However, recent studies have demonstrated that electrolyte decomposition does occur and generates surface films on the LTO surface, even when the cell is operated within the stability window of the common salts and solvents used in LIBs [23][24][25][26][27][28]. Song et al [27] reported the formation of a surface film on an LTO surface, which is significantly enhanced by the presence of conductive carbon in the composite LTO electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…) and the inherently sluggish lithium-ion diffusion coef cient of bulk LTO greatly limit its rate capability, as well as its practical implementation [4][5][6][7][8][9] . The improvement for the rate performance of Li 4 Ti 5 O 12 anode have been widely studied over the past decade, which can be roughly divided into two strategies.…”
Section: Introductionmentioning
confidence: 99%